Literary Texts Strategies of Teaching to Improve Portuguese Skills in Basic Education - Pinto de Fatima Ximenes, Jenito (Universitas Cokroaminoto Palopo, 2025)
This study aims to investigate the pedagogical strategies used to teach literary texts in basic education in Timor-Leste, with a focus on less-explored genres such as poetry, fables, traditional tales, prayers (hamulak), and legends. Based on a literature review, various didactic strategies were identified, including the use of audiovisual resources, debate circles, educational games, and reading and retelling texts. These strategies can serve as facilitating tools in Portuguese language instruction, allowing basic education teachers to enrich their pedagogical knowledge and promote the development of essential linguistic skills for students' academic and personal growth in Timor-Leste and the Lusophone community.The research was conducted at Santa Úrsula Basic Education School in Baucau. There were seven (7) participants: one Portuguese language teacher and six (6) students from grades 7, 8, and 9. The sample was selected using purposive sampling, choosing participants with specific knowledge of the phenomenon under investigation. The methods used were observation, document analysis, and semi-structured interviews. The data will be interpreted qualitatively using thematic analysis to understand the impact of these strategies on student learning. The results show that the teacher uses various strategies, including content adaptation and the use of the Tetum language as a support language to overcome linguistic barriers. However, the research identified infrastructure limitations and the need for increased use of interactive methodologies, such as dramatization and games, which students strongly desire. The study concludes that literature teaching in Timor-Leste requires a multilingual and multicultural approach, with cooperation among teachers, schools, and institutions to improve the quality of education.